2020
DOI: 10.3390/polym12061372
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Vanadium Redox Flow Battery by Treated Carbon Felt Electrodes of Polyacrylonitrile using Atmospheric Pressure Plasma

Abstract: A high-performance carbon felt electrode for all-vanadium redox flow battery (VRFB) systems is prepared via low-temperature atmospheric pressure plasma treatment in air to improve the hydrophilicity and surface area of bare carbon felt of polyacrylonitrile and increase the contact potential between vanadium ions, so as to reduce the overpotential generated by the electrochemical reaction gap. Brunauer-Emmett-Teller (BET) surface area of the modified carbon felt is, significantly, five times higher than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Moreover, for APPJ-treated GFs, the voltage obtained with the APPJ 550 • C was slightly higher than that with the APPJ 450 • C. However, the obtained voltage dropped to lower values when the treatment temperature was further increased to 650 • C (for APPJ 650 • C). Lin et al [27] observed that, for the CF electrodes treated with APPJ multiple times, although the APPJ treatment enhanced the hydrophilicity, it decreased the electronic conductivity of the felt. In the present study, although no electronic conductivity measurement was performed, the changes in the overall graphitic nature of various APPJ-treated GFs, as previously discussed based on the XPS data in Section 3.1, can be considered as an indicative of the potential electronic conductivity of the APPJ-treated GFs, where the graphitic nature of the GF increased upon increasing the APPJ treatment temperature from 450 • C to 550 • C but then decreased for AAPJ 650 • C. Nevertheless, this indicates that the APPJ treatment temperature may have a tradeoff effect between surface functionalization and wettability, as well as between surface degradation and electronic conductivity of the GF electrodes [27,45]; therefore, careful considerations must be kept in mind in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, for APPJ-treated GFs, the voltage obtained with the APPJ 550 • C was slightly higher than that with the APPJ 450 • C. However, the obtained voltage dropped to lower values when the treatment temperature was further increased to 650 • C (for APPJ 650 • C). Lin et al [27] observed that, for the CF electrodes treated with APPJ multiple times, although the APPJ treatment enhanced the hydrophilicity, it decreased the electronic conductivity of the felt. In the present study, although no electronic conductivity measurement was performed, the changes in the overall graphitic nature of various APPJ-treated GFs, as previously discussed based on the XPS data in Section 3.1, can be considered as an indicative of the potential electronic conductivity of the APPJ-treated GFs, where the graphitic nature of the GF increased upon increasing the APPJ treatment temperature from 450 • C to 550 • C but then decreased for AAPJ 650 • C. Nevertheless, this indicates that the APPJ treatment temperature may have a tradeoff effect between surface functionalization and wettability, as well as between surface degradation and electronic conductivity of the GF electrodes [27,45]; therefore, careful considerations must be kept in mind in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Materials 2021, 14, x FOR PEER REVIEW 10 of 14 that of the APPJ-treated CF electrodes [27] and GF electrodes [28], but it was lower than that of the low-pressure plasma-treated graphene-incorporated GF electrodes recently reported by Bellani et al [42], which could be attributed to the additional contribution of incorporated graphene toward an expected enhancement in catalytic and electronic conductivity. Figure 6d shows that the discharge capacity slightly decreased with the cycling number.…”
Section: Effect Of Treatment Methods On Limiting Current Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to flow field impacts, the electrode is one of the most critical components since electrochemical reactions occur on the electrode surface. Many studies have attempted to improve ion transport by modifying electrode structure (thickness, porosity, and tortuosity) [35,[44][45][46][47][48]. However, there is a sensitive balance between permeability and electrochemical surface area in the electrode; in general, higher permeability is achieved at the cost of reduced active surface area.…”
Section: Introductionmentioning
confidence: 99%